Anti-Müllerian hormone signalling sustains circadian homeostasis in zebrafish - Qiaohong Lin; Xian Du; Fan Ren; Ying Liu; Gaorui Gong; Si Ge; Weiwei Li; Zhi Li; Li Zhou; Ming Duan; Xi-Yin Li; Guang-Zhong Wang; et al. (Nature Communications)
Abstract Circadian clocks temporally orchestrate the behavioural and physiological rhythms. The core molecules establishing the circadian clock are clear; however, the critical signalling pathways that cause or favour the homeostasis are poorly understood. Here, we report that anti-Müllerian hormone (Amh)-mediated signalling plays an important role in sustaining circadian homeostasis in zebrafish. Notably, amh knockout dampens molecular clock oscillations and disrupts both behavioural and hormonal circadian rhythms, which are recapitulated in bmpr2a null mutants. Somatotropes and gonadotropes are identified as Amh-targeted pituitary cell populations. Single-cell transcriptome analysis further reveals a lineage-specific regulation of pituitary clock by Amh. Moreover, Amh-induced effect on clock gene expression can be abolished by blocking Smad1/5/9 phosphorylation and bmpr2a knockout. Mechanistically, Amh binds to its receptors, Bmpr2a/Bmpr1bb, which in turn activate Smad1/5/9 by phosphorylation and promote circadian gene expression. Our findings reveal a key hormone signalling pathway for circadian homeostasis in zebrafish with implications for rhythmic organ functions and circadian health.